2013
DOI: 10.1002/ejoc.201300379
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot, Regioselective Consecutive Multihalogenation of 2,2′‐Bithiophene

Abstract: The one‐pot regioselective consecutive multihalogenation of 2,2′‐bithiophene (1) was demonstrated. Compound 1 was consecutively halogenated with lithium halides such as lithium bromide, chloride, and/or iodide in the presence of lead tetraacetate in chloroform at room temperature or under reflux conditions to give 5‐bromo(or chloro)‐5′‐iodo(or chloro)‐, 3‐bromo(or chloro)‐5,5′‐dibromo(or dichloro, diiodo)‐, 3,3′‐dibromo‐(or dichloro)‐5,5′‐diiodo(or dibromo, dichloro)‐, and 3,3′,5‐tribromo(or trichloro)‐5′‐iodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The PCPO25 host material was designed to take advantage of the merits of good charge transport properties and low bandgap of substitution at 2-position of carbazole, and high glass transition temperature and high quantum effi ciency of substitution at 4-position of carbazole. [ 14 ] It was reported that substitution of diphenylphosphine oxide at 2-position of carbazole reduced the bandgap and increased charge transport properties because of deepened LUMO level, resulting in low driving voltage and high power effi ciency in blue PHOLEDs. [ 17 ] On the other hand, the substitution of diphenylphosphine oxide at 4-position of carbazole was effective to increase the glass transition temperature and quantum effi ciency of blue PHOLEDs due to steric hindrance and balanced charge density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCPO25 host material was designed to take advantage of the merits of good charge transport properties and low bandgap of substitution at 2-position of carbazole, and high glass transition temperature and high quantum effi ciency of substitution at 4-position of carbazole. [ 14 ] It was reported that substitution of diphenylphosphine oxide at 2-position of carbazole reduced the bandgap and increased charge transport properties because of deepened LUMO level, resulting in low driving voltage and high power effi ciency in blue PHOLEDs. [ 17 ] On the other hand, the substitution of diphenylphosphine oxide at 4-position of carbazole was effective to increase the glass transition temperature and quantum effi ciency of blue PHOLEDs due to steric hindrance and balanced charge density.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] On the other hand, the substitution of diphenylphosphine oxide at 4-position of carbazole was effective to increase the glass transition temperature and quantum effi ciency of blue PHOLEDs due to steric hindrance and balanced charge density. [ 14 ] Therefore, the substitution of the diphenylphosphine oxide at 2-and 5-positions may have synergic effect on the thermal stability, low driving voltage and high quantum effi ciency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial effort was directed towards thiophene and benzothiophene derivatives that would leadt op olycyclic structures, which are widelyp resenti nf unctional organic materials. [29] Thus, for our study we chose the 3,3'-dibromo-2,2'-bithiophene 17 a [30] and the 3,3'-2,2'-dibenzodithiophene 17 b. [31] Delightfully,t he autotandem cascade reactions with 17 a proceeded as expected to yield spirodithiophenes [32] 18 with moderate to good yields (Scheme 11).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 3Dd was carried out as described for the synthesis of 3Aa from 2-chlorothiophene (1d; 2.58 g, 21.8 mmol), TMPMgCl•LiCl (1 M in THF, 26.1 mL, 26.1 mmol), 2-bromothiophene (2D; 2.50 mL, 26.1 mmol) and Pd-PEPPSI-SIPr (0.11 mg, 0.16 mmol) in THF (50 mL) at 60 °C for 24 h. The 1 H NMR spectrum was identical to that reported previously. 18 Yield: 76%; light-yellow solid. 1 H NMR (400 MHz, CDCl 3 ): δ = 6.83 (d, J = 4.1 Hz, 1 H), 6.93 (d, J = 4.1 Hz, 1 H), 7.01 (dd, J = 3.7, 5.0 Hz,1 H), 7.10 (dd, J = 0.9, 3.7 Hz, 1 H), 7.22 (dd, J = 1.4, 5.0 Hz, 1 H).…”
Section: -Chloro-5-(thiophen-2-yl)thiophene (3dd)mentioning
confidence: 99%